2004
DOI: 10.1097/01.alc.0000139829.67958.1a
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Central Administration of a Selective Neuropeptide Y Y1 Receptor Antagonist Suppresses Ethanol Intake by C57BL/6J Mice

Abstract: These data indicate that acute blockade of the NPY Y1 receptor with a systemically bioavailable NPY Y1RA reduces voluntary ethanol consumption by C57BL/6J mice. These results are consistent with observations that hypothalamic infusion of NPY increases ethanol drinking by rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…Mouse studies indicate that Y 1 Rs mediate the suppressive effects of NPY on alcohol drinking (Thiele et al 2002;Sparta et al 2004;Eva et al 2006). Likewise, acute stress and alcohol withdrawal increase amygdalar Y 1 R expression in rodents (Aguilar-Valles et al 2005;Eva et al 2006;Sommer et al 2008).…”
Section: Neuropeptide Y (Npy) and Alcohol-related Behaviormentioning
confidence: 99%
“…Mouse studies indicate that Y 1 Rs mediate the suppressive effects of NPY on alcohol drinking (Thiele et al 2002;Sparta et al 2004;Eva et al 2006). Likewise, acute stress and alcohol withdrawal increase amygdalar Y 1 R expression in rodents (Aguilar-Valles et al 2005;Eva et al 2006;Sommer et al 2008).…”
Section: Neuropeptide Y (Npy) and Alcohol-related Behaviormentioning
confidence: 99%
“…Among these, Y 1 , Y 2 , and Y 5 receptors are implicated in modulation of alcohol intake [147 ]. Recent studies showed the NPY Y 1 receptor antagonist to suppress alcohol intake in mice [152]. A naturally occurring functional polymorphism of an NPY receptor-like protein gene (npr-1) in Caenorhabditis elegans negatively regulated the development of acute tolerance [153 ].…”
Section: Neuropeptide Y and Neuropeptide Y Receptorsmentioning
confidence: 99%
“…Neuropeptide Y (NPY) is a 36 amino acid neurotransmitter that is distributed widely in the brain and has been shown to be involved in a variety of biological functions, including food intake, seizure activity, cardiovascular homeostasis, integration of emotional behaviour, thermogenesis and circadian rhythms [152,153]. NPY appears to have functions opposite to those of CRF [154].…”
Section: Neuropeptide Y Agonists/antagonistsmentioning
confidence: 99%
“…In particular, the Y 1 receptor appears to play a role in altering alcohol intake as well as some of the intoxicating effects of alcohol [155]. Blockage of NPY 1 receptors with selective Y 1 antagonists BIBP-3226 and (-)-2-[1-(3-chloro-5-isopropyloxycarbonylaminophenyl)ethylamino]-6-[2-(5-ethyl-4-methyl-1,3-tiazol-2-yl)ethyl]-4-morpholinopyridine reduced alcohol consumption as well as motivation to self-administer alcohol in mice and rats [153,156]. The presynaptic Y 2 receptor may also modulate alcohol drinking behaviour.…”
Section: Neuropeptide Y Agonists/antagonistsmentioning
confidence: 99%